Black Holes and the Event Horizon as a Sample of the Scientific Astronomical Miraculousness in the Holy Quran - M. Jarad , Dr. Majeed (International Journal of Psychosocial Rehabilitation, 2020)
The Holy Qur’an spoke in many verses about things that science came after many years to prove them. Among these issues were matters related to astronomy, the locations of stars, and the types of these stars, and others. In this research, the focus is on the newly discovered black holes as a model of the astronomical scientific miraculousness in the Holy Qur’an, and in order to make the image clearer in the glory of this miraculousness. The present research begins by explaining how some stars evolved into black holes, as the research points to specifications and the features that distinguish the black hole and how the Holy Qur’an spoke more than 1400 years ago in many verses about this creature and described it as a faint and subtle star, meaning that this star cannot been seen and that it is in a constant running and it sweeps the sky, as it was mentioned in the noble verse (No! I swear by the slinkers, the runners, the sinkers) (Al-Takwir: 15-16) in which Almighty Allah swore by the of the revelation of the holy Qur’an. This credibility is in full conformity with what has been proven by modern science in the field of astronomy and space research at the present time, which is one of the modern scientific astronomical discoveries. Thus, science reveals to us whenever it offers hidden secrets for this strange universe that the Qur’an spoke about hundreds years ago.